Jews and Germans in Eastern Europe : shared and comparative histories - Grill, Tobias HerausgeberIn (New perspectives on modern Jewish history, 2018)
For many centuries Jews and Germans were economically and culturally of significant importance in East-Central and Eastern Europe. Since both groups had a very similar background of origin (Central Europe) and spoke languages which are related to each other (German/Yiddish), the question arises to what extent Jews and Germans in Eastern Europe share common historical developments and experiences. This volume aims to explore not only entanglements and interdependences of Jews and Germans in Eastern Europe from the late middle ages to the 20th century, but also comparative aspects of these two communities. Moreover, the perception of Jews as Germans in this region is also discussed in detail.